2022
DOI: 10.3390/neuroglia3040009
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Cells for Spinal Cord Injury: The Cellular Superpowers for Nerve Repair

Abstract: Neurotrauma injuries are notoriously difficult to deal with both clinically as well as experimentally, as the cellular and molecular events ensuing after injury complicate the neuroinflammatory processes. Spinal cord injuries are further complicated by the formation of scars at the injury sites, which can provide a physical barrier to repair. The lack of effective clinical therapy for spinal cord injury underscores the need for experimental approaches to generate effective therapies. To repair the injury, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other studies have shown the presence of unidentified cell populations involved in SCI repair in addition to NSCs or stem-like cells with a differentiation capacity [ 59 , 60 ]. Therefore, recent studies have reported mixed cell populations that may participate in nerve regeneration, including Schwann cells [ 61 ], olfactory ensheathing cells [ 62 ], and neurotrophin-expressing fibroblasts, such as BDNF and NT-3 [ 63 ]. At present, however, a definitive analysis of cell populations engaged in nerve regeneration is difficult for two reasons.…”
Section: Current Challenges In the Treatment Of Scismentioning
confidence: 99%
“…Other studies have shown the presence of unidentified cell populations involved in SCI repair in addition to NSCs or stem-like cells with a differentiation capacity [ 59 , 60 ]. Therefore, recent studies have reported mixed cell populations that may participate in nerve regeneration, including Schwann cells [ 61 ], olfactory ensheathing cells [ 62 ], and neurotrophin-expressing fibroblasts, such as BDNF and NT-3 [ 63 ]. At present, however, a definitive analysis of cell populations engaged in nerve regeneration is difficult for two reasons.…”
Section: Current Challenges In the Treatment Of Scismentioning
confidence: 99%
“…The biological approaches offer the opportunity to replace the lost neural tissue mass and mitigate the damage by shrinking the defect size. Out of all the stem and non-stem cell types explored for cell transplantation, olfactory ensheathing cells (OECs) stand out as promising candidates for neural repair due to their unique properties [ 12 , 13 ]. The OECs are the primary glial cells of the olfactory nerve, where they play a crucial role in replacing up to 1–3% of olfactory neurons daily and guide them to their intended targets in the olfactory bulb throughout life [ 14 ].…”
Section: Introductionmentioning
confidence: 99%